2011
DOI: 10.1111/j.1365-2672.2011.04963.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory activities of specific bacterial secondary metabolite ofAnoxybacillus flavithermusstrain SX-4 on carp,Cyprinus carpio

et al.

Abstract: Aims:  To determine the capacity of secondary metabolite of strain SX‐4, to enhance the nonspecific immunity and survival of carp (Cyprinus carpio), and to identify the constituents that are responsible. Methods and Results:  A thermophilic strain SX‐4 that is able to produce immunostimulatory metabolite was isolated from sludge sample of hot spring and identified by comparison with 16S rRNA sequences (99% of homology) as Anoxybacillus flavithermus. Bioactivity‐guided fractionation of methanol extract from its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(71 reference statements)
0
7
0
1
Order By: Relevance
“…Recently, bacterial secondary metabolites have received greater attention for disease control in fish aquaculture. Liu et al (2011) demonstrated that secondary metabolite cyclo-( L -Pro-Gly), isolated from Anoxybacillus flavithermus SX-4 could enhance non-specific immunity and disease resistance in carp ( Cyprinus carpio ). Isolated secondary metabolites from the soil isolate B. simplex increased cytokine responses and disease resistance against Aeromonas hydrophila challenge in C. carpio (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bacterial secondary metabolites have received greater attention for disease control in fish aquaculture. Liu et al (2011) demonstrated that secondary metabolite cyclo-( L -Pro-Gly), isolated from Anoxybacillus flavithermus SX-4 could enhance non-specific immunity and disease resistance in carp ( Cyprinus carpio ). Isolated secondary metabolites from the soil isolate B. simplex increased cytokine responses and disease resistance against Aeromonas hydrophila challenge in C. carpio (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . () determined the capacity of the secondary metabolite cyclo‐( l ‐Pro‐Gly), isolated from Anoxybacillus flavithermus SX‐4, to enhance the nonspecific immunity and disease resistance of carp ( C. carpio ). After intraperitoneal administration of this compound, selected innate immune parameters including superoxide anion production, phagocytic activity and serum lysozyme activity, along with immune‐related gene expression (i.e.…”
Section: Bacterial Secondary Metabolites As Fish Immunostimulantsmentioning
confidence: 99%
“…У карпа и белого амура зарегистрирована очень низкая активность фермента: от следовых величин до 1,75 мкг/мл (Yang et al, 2008;Ardo et al, 2010;Liu et al, 2011;Weifen et al, 2012). Относительно низкую лизоцимную активность -3,3-13 мкг/млпроявляют сыворотки тропических карповых L. rohita и Puntius sarana (Swain et al, 2007;Dash et al, 2011;Behera, Swain, 2012;Das et al, 2012).…”
Section: результаты и обсуждениеunclassified